2015
DOI: 10.1017/s1751731114003279
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of nutrient intake, feed efficiency and performance in cattle grazing on tropical grasslands

Abstract: It is essential to quantify the potential of tropical grasslands to allow significant feed efficiency for grazing livestock in controlled conditions such as at pasture. We conducted a quantitative analysis of published studies reporting the experimental results of average daily gains (ADG) and diet characteristics obtained specifically under grazing conditions (17 publications and 41 experiments), which have been less studied compared with controlled conditions in stalls. The database was analyzed to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 54 publications
(48 reference statements)
2
18
0
6
Order By: Relevance
“…Animal production efficiency and profitability are determined by the genetic merit of animals for efficiency of nutrient utilisation and growth (Boval et al 2015;Chaokaur et al 2015). Pre-weaning is a very important stage in all domestic production systems focussed on meat production.…”
Section: Introductionmentioning
confidence: 99%
“…Animal production efficiency and profitability are determined by the genetic merit of animals for efficiency of nutrient utilisation and growth (Boval et al 2015;Chaokaur et al 2015). Pre-weaning is a very important stage in all domestic production systems focussed on meat production.…”
Section: Introductionmentioning
confidence: 99%
“…Ungerfeld et al (2007) identified outliers by removing data one by one, using an absolute studentised residual value over 2 standard deviations, or a leverage value over 2k/n (where k = number of independent variables and n = number of studies) or Cook's distance over 90%. Boval et al (2015) removed outliers that were greater than an absolute value of 3 of normalised residuals. Escobar-Bahamondes et al (2016) identified and excluded outliers by using Mahalanobis distance calculated from various dietary components, liveweight (LW), DMI and MP.…”
Section: Introductionmentioning
confidence: 99%
“…The high degradability of cactus organic matter (Tosto et al 2015;Siqueira et al 2017), which comprised 35% of DM of the TH and SB diets, may have increased the synthesis of organic acids (Lins et al 2016) and microbial protein in the rumen of the sheep, which explains the greater gain in weight. In a recent review, Boval et al (2015) verified that the weight gain increases as the digestible dry matter intake increases too.…”
Section: Discussionmentioning
confidence: 96%